Recreation: Perceptions, Views & Practices From A Developing Country - Waris Qidwai, Sidra ishaque, Marium Anis, Mohammed All Al Shafaee, Sana Gliani, Syed iqbal Azam (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2012)
Background: Anything that gives you peace of mind and happiness is deemed recreation. It is a positive change from the stereotypical lifestyle and involves an active participation in some entertaining activity. The need for recreational activities has doubled in the present times. We therefore conducted a survey to explore the various aspects of recreation in our population through this study. Methodology:A questionnaire based cross-sectional survey was performed in the Community Health Centre of a tertiary care teaching hospital in Pakistan. Data collection was done via a face-to-face interview based on a structured, pre-tested questionnaire. Participants included all willing persons between 18-75 years of age approached prior to their appointments at the Community Health Centre. Questions were developed at exploring patients’ knowledge, attitude and practices with regards to recreational activities. Results: A total of 320 responses were used for the survey. The majority of the participants (98.8%) were of the opinion that recreational activities are important for health maintenance. However, less than half of them (156/320) thought that separate time should be allocated for recreational activities. Travelling came up to be the most favourite of all recreational activities. Satisfaction with family life was the most common reason for somebody to enjoy life. (24.7%) thought that the harm related to recreation depended on the type of activity. Conclusion: Recreation needs to be acknowledged as an important part of an individual’s life. Tourism industry needs to be developed. Efforts need to be geared towards the promotion of recreational activities on a larger scale. We recommend that guidelines need to be developed pertaining to the recreational requirements of individuals.